Nrf2 activator via interference of Nrf2-Keap1 interaction has antioxidant and anti-inflammatory properties in Parkinson's disease animal model - Kim, Siwon; Viswanath, Ambily Nath Indu; Park, Jong-Hyun; Lee, Ha Eun; Park, A. Yeong; Choi, Ji Won; Kim, Hyeon Jeong; Londhe, Ashwini M.; Jang, Bo Ko; Lee, Jaeick; Hwang, Hayoung; Lim, Sang Min; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by abnormal movement, including slowed movements, shuffling gait, lack of balance, and tremor. Oxidative stress has been shown to play a decisive role in dopaminergic neuronal cell death in PD. The nuclear factor E2-related factor 2 (Nrf2)-Kelch-like ECH-associated protein 1 (Keap1) signaling pathway provides the main defense system against oxidative stress by inducing the expression of antioxidant enzyme genes. Direct interference in the Keap1-Nrf2 protein-protein interaction (PPI) has emerged as an effective strategy for Nrf2 activation. Therefore, we searched for novel Nrf2 activators that can disrupt Nrf2-Keap1 interaction by using a virtual screening approach and identified a potent Nrf2 activator, KKPA4026. KKPA4026 was confirmed to induce the expression of the Nrf2-dependent antioxidant enzymes heme oxygenase-1, glutamate-cysteine ligase catalytic subunit, glutamate-cysteine ligase regulatory subunit, and NAD(P)H:quinone oxidoreductase 1 in BV-2 cells. Furthermore, KKPA4026 showed anti-inflammatory effects in an Nrf2-dependent manner. In a 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)induced mouse model of PD, KKPA4026 effectively attenuated PD-associated behavioral deficits and protected dopaminergic neurons. In summary, we identified KKPA4026 as a novel Nrf2 activator and suggested that Nrf2 activation through interference with the Nrf2-Keap1 interaction may be effective for PD treatment.